Probabilistic security analysis through path-based metric evaluation in wireless sensor networks - Kumar Pattem, Sampath; K, Jayasankar; V, Sumalatha (International Journal of Engineering and Technology, 2018)
This paper analyzes the possible security threats in the wireless sensor network (WSN) through the path based metrics. Since the routing in WSN focuses towards the energy optimizing by which an optimal path is selected which consumes less energy. However security is also very important in WSN which won’t considers in the optimal path selection. This paper analyzes the possible security threats based on the characteristics of paths. A simple comparative analysis is carried out in this paper between different topologies of network through the path based metrics. Since there exists number of path metrics, some metrics are categorized as decisive and some are assistive and based on the obtained count, one network topology is finalized as more secure. Matlab is used for the Realization of this methodology.